Psychic Determinism: An Analysis of Michael Henchard’s Character in Thomas Hardy’s The Mayor of Casterbridge - Bahisht, Samra; Afzal, Amna (Pakistan Languages and Humanities Review, 2024)
This research paper aims to discuss the willfulness of Michael Henchard in the novel, The Mayor of Casterbridge. It explores the causes and role of will in his life, and emphasizes the role of free will in human suffering. The study applies Psychic Determination as theoretical framework for the analysis of the text. It analyses the character of Henchard to point out free will in the novel. The methodology adopted for this research is qualitative and descriptive. The data has been collected from primary and secondary sources. It explains how the story’s main character uses his will and what consequences he bears. Furthermore, it describes the reasons for the decisions made by Henchard. The close study and analysis of the text show that Henchard was a willful person and was responsible for his sufferings. The study proves that the role of human choice is an important factor in life. Other characters in this novel can be studied from another perspective. Besides, Thomas Hardy’s other novels provide good points to be explored for showing the importance of free will in his novels and human life.